TOXOLOGICAL REMEDIATION OF OXIDATIVE STRESS BY LEAF EXTRACT OF SPHAGNETICOLA TRILOBATA IN LYMPHOCYTE OF ORYCTOLAGUS CUNICULUS L. - HUSAIN , NISREEN; KUMAR, ANIL (The Bioscan, 2013)
Free radicals, generated by the various endogenous systems of our body, in the form of ROS and RNS adversely alter lipid, protein and DNA constitution by inducing damage in cells. This is due to toxic lipid peroxidation in biomembranes causing disruption in natural defense system of the body. Consequently, the condition of oxidative stress develops that lead to a number of diseases. Antioxidants neutralize the adverse effects of free radicals, thus preventing the conditions of pathogenecity. The naturally occurring antioxidant constituents of many plants act as radical scavengers and inhibitors of the toxicological process of oxidation. The antioxidant activity of leaf extract of Sphagneticola trilobata was evaluated in the present study, against hydrogen peroxide induced oxidative damage in lymphocytes of Oryctolagus cuniculus L. (Rabbit). Incubated lymphocytes with H2O2 for 2h, increased toxicity due to lipid peroxidation affecting the activities of MDA (4.69 ± 0.04), SOD (1.60 ± 0.03), GSH (2.48 ± 0.03), CAT (2.87 ± 0.03) and GPx(5.60 ± 0.10). Treatment with the extract of leaves of Sphagneticola trilobata for 18h was found to effectively inhibit (MDA 1.09 ± 0.03) or reduce lipid peroxidation and positively stimulate the activities of the antioxidant enzymes, SOD (3.39 ± 0.03), CAT (5.69 ± 0.05) and GPx (10.56 ± 0.02) and glutathione (5.26 ± 0.03) significantly usually with 20µL extract. The results, thus, indicated the free radical scavenging action of leaf extract of Sphagneticola trilobata to minimize toxicity.